1992
DOI: 10.1021/tx00030a022
|View full text |Cite
|
Sign up to set email alerts
|

A thermospray liquid chromatography/mass spectrometry method for analysis of human urine for the major malondialdehyde-guanine adduct

Abstract: A method is described for detection and quantitation of the major malondialdehyde-guanine adduct (M1G) based on thermospray liquid chromatography/mass spectrometry. A stable isotope analog of M1G ([2H2]M1G) was used as an internal standard. Thermospray mass spectra of M1G and [2H2]M1G showed intense protonated molecular (MH+) ions that were suitable for use in quantitation of M1G. M1G was purified from human urine and reduced with NaBH4 to a dihydro derivative that was cleanly separated from the contaminants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Furthermore, Seto detected M 1 G-R in urine and confirmed its structure by mass spectrometry (). There is a report of the detection of the base, M 1 G, in human urine by HPLC with fluorescence detection, but we were unable to confirm this finding by mass spectrometry ( , ).…”
Section: Discussioncontrasting
confidence: 66%
“…Furthermore, Seto detected M 1 G-R in urine and confirmed its structure by mass spectrometry (). There is a report of the detection of the base, M 1 G, in human urine by HPLC with fluorescence detection, but we were unable to confirm this finding by mass spectrometry ( , ).…”
Section: Discussioncontrasting
confidence: 66%
“…The low excretion level obtained with the immuno‐extraction LC/APCI‐MS/MS method, combined with the complexity of urine, have clearly demonstrated that detection and quantification of M 1 G‐dR in urine represent a major analytical challenge. This might explain the scarcity of data previously published on lipid peroxidation DNA adducts in humans, particularly urinary excretion 18, 20, 22. The measurement of M 1 G‐dR excretion rates in exposed individuals, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols for antibody preparation and immuno‐extraction are given in detail elsewhere 10, 12, 17. The purified sample was chemically reduced with 10 µl of 10 mg ml −1 NaBH 4 18. The reagent was removed on a 50 mg C 18 solid‐phase extraction column, vacuum centrifuged to dryness and dissolved in a final volume of 100 µl of 5 m M ammonium acetate buffer (pH 5.0) before LC/MS/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Of these markers, 8-OHdG has been widely used for the diagnosis of oxidative stress caused by smoking (Cooke et al, 2002(Cooke et al, , 2005Harman et al, 2003) and has also been reported as the DNA damage marker of cancer (Kasai, 2003;Cooke et al, 2005), Parkinson's disease (Sato et al, 2005) and Alzheimer's disease (de la Monte et al, 2000). Urinary 8-OH-dG has been monitored by gas chromatographymass spectrometry (GC-MS; Teixeira et al, 1995), high-performance liquid chromatography with electrochemical detection (HPLC-ECD; Cooke et al, 2002;Kasai, 2003), HPLC with mass spectrometry (HPLC-MS; Harman et al, 2003;Jajoo et al, 1992) and enzymelinked immunoassay (ELISA; Chiou et al, 2003). HPLC-ECD required sample purification to avoid interferences from charged species in urine samples and required frequent maintenance of the cell electrode (Cooke et al, 2002, Kasai, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC-ECD required sample purification to avoid interferences from charged species in urine samples and required frequent maintenance of the cell electrode (Cooke et al, 2002, Kasai, 2003. HPLC-MS required the addition of expensive stable isotope-labeled internal standard (Harman et al, 2003;Jajoo et al, 1992). The urinary data by ELISA were higher than those from the HPLC-ECD method (Kasai et al, 2003), possibly because of the quality of the commercial monoclonal antibody.…”
Section: Introductionmentioning
confidence: 99%